A Challenge to African Christianity: Human Dignity Stance of Umunna Solidarity in Igbo Traditional Society - Clement I. Osunwokeh (Current Approaches in Science and Technology Research Vol. 1, 2021)
The fulcrum of social justice is the respect of human dignity. Before the Universal Declaration of Human Rights (UDHR) saw the light of the day in 1948, the pre-colonial Igbo people of Eastern Nigeria have already defined what constitutes the foundation of peaceable society. They invested the norms of human dignity on the umunna solidarity. Umunna is the assemblage of brethren born within an androgynous linage. In this social arrangement, individuals are lost as persons without the community, hence their popular cliché, “umunna is power.” This social arrangement protects the individuals from being dehumanized. Here everyone who belongs to the umunna receives a uniform treatment, the king and the subjects alike. It is in this context that human rights and dignity become community property. However, this pristine social arrangement has been lost consequent upon the contact and interaction of Igbo people with Western Christianity. The overwhelming consequences have become individualism of persons resulting to the vitiation of human rights and dignity of persons. Thus after a critical considerations of the entire vista, this paper notices that Christianity, despite its long contact with the Igbo people, has not taken any deep root and as such may not be consulted in serious matters in Igbo life and existence. It, therefore, proffers African Christianity, among other traditional values of human dignity, the community living and social solidarity of umunna of the Igbo people as major ways that Christianity can become relevant in Africa and among Africans. African Christianity has to rise to the challenge of a high level of objectivity in the religion’s practice of its adherents.